2016
DOI: 10.3390/md14010024
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography-Mass Spectrometry-Based Rapid Secondary-Metabolite Profiling of Marine Pseudoalteromonas sp. M2

Abstract: The ocean is a rich resource of flora, fauna, and food. A wild-type bacterial strain showing confluent growth on marine agar with antibacterial activity was isolated from marine water, identified using 16S rDNA sequence analysis as Pseudoalteromonas sp., and designated as strain M2. This strain was found to produce various secondary metabolites including quinolone alkaloids. Using high-resolution mass spectrometry (MS) and nuclear magnetic resonance (NMR) analysis, we identified nine secondary metabolites of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…SWAT5, Pseudoalteromonas piscicid a and Pseudoalteromonas sp. M2 were shown to attenuate the growth of Vibrio harveyi , V. anguillarum , a marine cyanobacterium of the genus Synechococcus , various diatom species, and the bloom‐forming coccolithophore Emiliania huxleyi (Wratten et al ., ; Long et al ., ; Harvey et al ., ; Kim et al ., ). HHQ and PQS production were also reported for P. bermudensis , a symbiont of the chlorophyte Tetraselmis striata .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…SWAT5, Pseudoalteromonas piscicid a and Pseudoalteromonas sp. M2 were shown to attenuate the growth of Vibrio harveyi , V. anguillarum , a marine cyanobacterium of the genus Synechococcus , various diatom species, and the bloom‐forming coccolithophore Emiliania huxleyi (Wratten et al ., ; Long et al ., ; Harvey et al ., ; Kim et al ., ). HHQ and PQS production were also reported for P. bermudensis , a symbiont of the chlorophyte Tetraselmis striata .…”
Section: Introductionmentioning
confidence: 97%
“…In particular, the complex ecosystems of biotic surfaces appear to promote the diversification of secondary metabolites to mediate dynamic inter-species and inter-domain interactions (Penesyan et al, 2010;Giordano et al, 2015). Among the variety of microbial secondary metabolites, 2-alkyl-1(H)-quinolin-4-ones [hereafter referred to as alkyl quinolones (AQs)] have been found to be produced by a number of marine representatives of the Pseudomonas, Alteromonas and Pseudoalteromonas clades as well as the Alphaproteobacterium Pelagibaca bermudensis (Wratten et al, 1977;Debitus et al, 1998;Bultel-Poncé et al, 1999;Long et al, 2003;Vynne et al, 2011;Whalen et al, 2015;Harvey et al, 2016;Kim et al, 2016;Patidar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that liquid chromatography–mass spectrometry-based rapid secondary-metabolite profiling of marine Pseudoalteromonas sp. M2, and isolated various pseudane compounds as secondary-metabolites, and found pseudane compounds has anti-melanogenic effect [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…IR spectra of the active compound showed peaks at 3448 , 300.15 cm -1 (O-H stretching), 2135.67 cm -1 (C-H alkane), 1714, 1640.38 cm -1 (C=O stretching), 1361.90, 1422.08 cm -1 (C= C aromatic), 1221,.28 1092.22 cm -1 (Aromatic C-O). The major chemical component Di-n-octyl phthalate was proven to have pharmaceutical uses as was reported by Kim et al (2004) who stated that phthalates which include butyl benzyl phthalate (BBP), di(n-butyl) phthalate (DBP), and di (2 ethylhexyl) phthalate (DEHP) had been demonstrated anticancer activity. Moreover, phenolic compounds exhibits antimicrobial activity (Patra and Baek, 2016;Rodríguez-Pérez et al, 2016;Marín et al, 2016;Tuberoso et al, 2016) and may reduce the risk of cardiovascular disease and stroke In these ways, phenolic compounds may also confer protection against chronic diseases such as atherosclerosis and assist in the management of menopausal symptoms.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Marine bacteria of the genus Pseudoalteromonas are recognized as major producers of various biologically active metabolites such as halogenated compounds, cyclic compounds, enzymes (Secun et al, 2015). Kim et al (2016) reported the production of various secondary metabolites from the genus Pseudoalteromonas against E.coli. …”
Section: Antibacterial Activity Of the Extracted Compoundsmentioning
confidence: 99%